Clinical Outcome of the Patients Treated Surgically for Malignant Middle Cerebral Artery Infarction (MMCAI) at Sawanpracharak Hospital - โล้วพฤกมณี, ณรงค์พงศ์ (Journal of Health Science of Thailand, 2025)
Abstract This study the relationship of factors associated with clinical outcome in surgical groups of malignant middle cerebral artery infarction (MMCAI). The data were retrospectively collected from surgically treated at Sawanpracharak Hospital between September 2012 and September 2023. All patients diagnosis malignant middle cerebral artery infarction (MMCAI). Decompressive hemicraniectomy (DHC) is one of the surgical options to treat. Patients who had history of disabling, neurological disease, stroke, secondary parenchymal hemorrhage, comorbidities preventing the surgery from being conducted such as renal and hepatic failure, use of warfarin and any coagulopathies, contraindication of the general anesthesia and surgery, pregnancy and any intracranial mass lesion were excluded from this study. This study was categorizes the treatment outcomes into 2 catagories: (1) survive, (2) dead were collected. In this study, there was statistically significant association between clinical outcome and GCS on admission, GCS on consultation, midline shift, sepsis and length of stay. Correlation coefficient between independent variable with functional outcome of MMCAI patients found that relationship between independent variable with functional outcome ≤ 0.80 (Stevens,1996), and no independent variable had multicollinearity. Correlation coefficient between independent variable with functional outcome of MMCAI patients. This research used independent variable which statistically significant; GCS on admission, GCS on consultation, midline shift, hospital stay and sepsis. Duration onset to operating room (D3) was the important factor in the clinical even though there is no statistically significant. After coefficient independent variable on clinical outcomes of MMCAI patients was done the present study found that there was statistically significant association between functional outcome and GCS on consultation [OR 1.26 (1.010-1.571); P=0.040)], duration onset to OR(D3) [OR 0.99 (0.975-0.977); P=0.016)], hospital stay [OR 1.12 (1.064-1.173); P=0.000)] and sepsis [OR 0.35 (0.010-0.115); P=0.000)]. The present study found that analysis of factors which affect on clinical outcomes of MMCAI patients were GCS on consultation [OR 1.374;P= 0.001], duration onset to OR(D3) [OR 0.968; P=0.009], length of stay [OR 1.121;P=0.000] and sepsis [OR 0.034;P=0.000]. Keywords: malignant middle cerebral artery infarction, decompressive hemicraniectomy, Glasgow come scale, Glasgow outcome scale